2016
DOI: 10.3389/fpls.2016.01243
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Volatiles Profile and Contents of Trichothecenes Group B, Ergosterol, and ATP of Bread Wheat, Durum Wheat, and Triticale Grain Naturally Contaminated by Mycobiota

Abstract: In natural conditions cereals can be infested by pathogenic fungi. These can reduce the grain yield and quality by contamination with mycotoxins which are harmful for plants, animals, and humans. To date, performed studies of the compounds profile have allowed for the distinction of individual species of fungi. The aim of this study was to determine the profile of volatile compounds and trichothecenes of group B, ergosterol, adenosine triphosphate content carried out on a representative sample of 16 genotypes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 48 publications
(67 reference statements)
1
15
0
Order By: Relevance
“…Nonanal and 2,4-decadienal, (E,E)- have a musty and unpleasant fried oil off-odour [ 10 , 25 ]. The mVOCs alcohols (1-pentanol; 2-furanmethanol and 1-octen-3-ol), ketones (2-heptanone), nitrogen compounds (pyrazine; pyrazine, methyl-), heterocyclic compounds (furan, 2-pentyl-), and other types of compounds (2(3H)-furanone, 5-ethyldihydro-) have been found in fungal spoilage grains [ 30 , 31 ]. Furthermore, these studies also suggested several of these mVOCs have low odour thresholds, which means they are volatilised at relatively low concentrations and could potentially be more readily detected by animals as an odour indicating spoiled and potentially toxic feed.…”
Section: Discussionmentioning
confidence: 99%
“…Nonanal and 2,4-decadienal, (E,E)- have a musty and unpleasant fried oil off-odour [ 10 , 25 ]. The mVOCs alcohols (1-pentanol; 2-furanmethanol and 1-octen-3-ol), ketones (2-heptanone), nitrogen compounds (pyrazine; pyrazine, methyl-), heterocyclic compounds (furan, 2-pentyl-), and other types of compounds (2(3H)-furanone, 5-ethyldihydro-) have been found in fungal spoilage grains [ 30 , 31 ]. Furthermore, these studies also suggested several of these mVOCs have low odour thresholds, which means they are volatilised at relatively low concentrations and could potentially be more readily detected by animals as an odour indicating spoiled and potentially toxic feed.…”
Section: Discussionmentioning
confidence: 99%
“…This was indicated by twice-higher ergosterol content (the total fungal quantity meter) and a three-fold higher Fusarium biomass content in organic grain. The content of ergosterol in grain depends on the type of grain (hulled, hull-less), cereal species and on the level of contamination of the grain with microscopic fungi, both pathogenic strains and native mycobiota [31,40,41]. Its content is affected also by the method of cultivation resulting from the use of fertilizers and treatments related to the use of plant protection chemicals [30].…”
Section: Discussionmentioning
confidence: 99%
“…Besides harvest losses, a major issue is the formation of mycotoxins. In addition to the nonvolatile mycotoxin metabolites, a wide spectrum of 50 volatile and 53 semivolatile metabolites (microbial volatile organic compounds [mVOC]) is also produced by different Fusarium species . An important class of semivolatile metabolites are the sesquiterpenes, which serve as building blocks in the biosynthesis of mycotoxins .…”
Section: Introductionmentioning
confidence: 99%